Memory Politics on Screen: The Aesthetics of Historical Trauma in Izaokas (Isaac) (2019) - Norkūnaitė, Gabrielė (Politologija, 2023)
This article analyses the Lithuanian feature film Izaokas (Isaac, 2018) as an expression of memory activism. The film actualised heated debates on a national level over the role of ordinary Lithuanians in the Holocaust and collaboration with Nazi Germany, in spite of the fact that the filmmakers did not intend to engage in historical debates. Nonetheless, by generating an immersive experience and engaging viewers at the level of affect, the film effectively engages in polemics with public narratives of the Second World War.
Keywords: Holocaust; memory activism; memory mapping; public history; World War II